Improved water supply and water handling technologies: Revealed complements but perceived substitutes for safe water quality. (2022) - Gross, Elena; Guenther, Isabel; Schipper, Youdi
Abstract: We analyze the impact of public water infrastructure and water handling technologies on the water quality and water handling behavior of households in rural Benin using both quasi-experimental and experimental household-level panel data. We find that the installation of improved village-level water sources induces households to reduce water disinfection efforts at home, indicating that households perceive improved public water infrastructure as a substitute for improved water handling to obtain safe drinking water. Consequently, point-of-use drinking water quality does not change. A reduction of contamination with E. coli at points of use can only be achieved if interventions providing drinking water technologies at the water source are complemented by household-level interventions and efforts to teach households how to maintain good water quality. Highlights: Experimental study on public water supply and private water handling technology in rural Benin. Installing improved water source in villages does not improve water quality in households. Water source provision as standalone intervention has adverse effect on hygienic water handling. Households reduce or stop water treatment practices when using improved sources. Water programs need to systematically transfer the quality of water from sources to households.